Direct visual internal urethrotomy for isolated, post-urethroplasty strictures: a retrospective analysis. (February 2017) - Brown, Elizabeth Timbrook; Mock, Stephen; Dmochowski, Roger; Reynolds, W. Stuart; Milam, Douglas; Kaufman, Melissa R.
Background: Urethroplasty is often successful for the treatment of male urethral stricture disease, but limited data exists on recurrence management. Our goal was to evaluate direct visual internal urethrotomy (DVIU) as a treatment option for isolated, recurrent strictures after urethroplasty. Methods: We retrospectively identified male patients who underwent urethroplasty from 1999 to 2013 and developed an isolated, recurrent stricture at the urethroplasty site treated with DVIU. Success was defined as lack of symptomatology and no subsequent intervention. Comparative analysis identified characteristics and stricture properties associated with success. Results: A total of 436 urethroplasties were performed in 401 patients at our institution between 1999 and 2013. Stricture recurrence was noted in 64 (16%) patients. Of these, 47 (73%) underwent a DVIU. A total of 37 patients met inclusion criteria and underwent 50 DVIU procedures at the urethroplasty site. A single DVIU was successful in 13 of 37 patients (35%). A total of 4 of 6 patients required a second DVIU (67%). Overall, 17 of 43 (40%) of the total DVIUs were successful after urethroplasty. Success did not differ by age, stricture length or location, surgical technique, radiation history, prior urethroplasty or DVIU, time to failure, or etiology. Conclusions: Post-urethroplasty DVIU for isolated, recurrent strictures may be offered as a minimally invasive treatment option. Approximately 40% of patients were spared further intervention.